STUDY OF HYDRAULIC FRACTURING OPERATION IN THE HTFN 11 WELL, HASSI MESSAOUD FIELD - SEBGAG Mohamed Islam; SAHLI Ibrahim; ABDELMOUIZ Ahmed (Amar Thelidji University - Laghouat FACULTY: Technology DEPARTMENT: PROCESS ENGINEERING, 2025)
This study focuses on the application of hydraulic fracturing supported by coiled tubing in the HTFN 11 well of the Hassi Messaoud field. Initially, the well exhibited a very low and unstable oil flow rate of about 0.8 m³/h, with a gas production of around 89.91. After the design and execution of the operation, including pre-job preparations, acid stimulation, and the main fracturing stage with 66,812 lbs of HSP 20/40 proppant, post-treatment measurements showed significant improvements: the oil flow rate increased by nearly 1.65 m³/h, reaching 2.45 m³/h, while gas production jumped to approximately 356.23. Economically, the total cost of the operation was about $192,429, with a payback period not exceeding 17 days at an oil price of $45/bbl. These results confirm the effectiveness of hydraulic fracturing in enhancing well productivity and highlight the complementary role of coiled tubing in ensuring operational success.
OPTION : Gas Engineering